Evolutionary Processes in the Emergence and Recent Spread of the Syphilis Agent, Treponema pallidum - Pla-Díaz, Marta; Sánchez-Busó, Leonor; Giacani, Lorenzo; Šmajs, David; Bosshard, Philipp P; Bagheri, Homayoun C; Schuenemann, Verena J; Nieselt, Kay; Arora, Natasha; González-Candelas, Fernando (Molecular biology and evolution, 2022)
The incidence of syphilis has risen worldwide in the last decade in spite of being an easily treated infection. The causative agent of this sexually transmitted disease is the bacterium Treponema pallidum subspecies pallidum (TPA), very closely related to subsp. pertenue (TPE) and endemicum (TEN), responsible for the human treponematoses yaws and bejel, respectively. Although much focus has been placed on the question of the spatial and temporary origins of TPA, the processes driving the evolution and epidemiological spread of TPA since its divergence from TPE and TEN are not well understood. Here, we investigate the effects of recombination and selection as forces of genetic diversity and differentiation acting during the evolution of T. pallidum subspecies. Using a custom-tailored procedure, named phylogenetic incongruence method, with 75 complete genome sequences, we found strong evidence for recombination among the T. pallidum subspecies, involving 12 genes and 21 events. In most cases, only one recombination event per gene was detected and all but one event corresponded to intersubspecies transfers, from TPE/TEN to TPA. We found a clear signal of natural selection acting on the recombinant genes, which is more intense in their recombinant regions. The phylogenetic location of the recombination events detected and the functional role of the genes with signals of positive selection suggest that these evolutionary processes had a key role in the evolution and recent expansion of the syphilis bacteria and significant implications for the selection of vaccine candidates and the design of a broadly protective syphilis vaccine.
Keywords: Syphilis; Yaws; frambézie; selection; treponematoses; Treponema pallidum; Humans; syfilis; recombination; lidé; Phylogeny; Treponemal Infections; fylogeneze; genome analysis; phylogenetic congruence; infekce bakteriemi rodu Treponema